Development of e-LKPD based on high order thinking skills (HOTS) to improve cultural literacy in folklore text material - Farahiba, Ayyu Subhi (IAIN Salatiga, 2021)
This research aims to develop hots-based e-LKPD as teaching material for learners to be able to understand the text material of folklore well. The method used in this research is the development (RD) of Borg and Gall which is simplified into seven stages, namely (1) potential and problems; (2) data collection; (3) product development; (4) product evaluation; (5) revision; (6) product trials; and (7) final revisions. Expert validation results show this HOTS-based e-LKPD has been worth using with revisions. The results of the trial showed that as many as 70% of students were able to solve high-level questions, 80% of students solved moderate-level questions, and 90% of students solved low-level questions. The results of the response questionnaire showed e-LKPD in the high category so that the percentage of ministry was obtained by 87.4% with very interesting criteria on all aspects measured, namely material aspect 87.2%, presentation aspect 86%, and language aspect 89%. The overall number of such percentages reaches very high criteria so, it can be concluded that the e-LKPD developed is very interesting and makes it easier for students to understand the material.